THE DETERMINATION OF RHEOLOGICAL OPTIMUM OF VAGINAL GELS - M. N. Anurova; E. O. Bakhrushina; A. M. Podkolzin; S. P. Krechetov (Разработка и регистрация лекарственных средств)
The article presents the results of rheological properties study of vaginal gels, registered in the Russian Federation. Was justified the optimal rheological characteristics, which can be recommended for use to the pharmaceutical development of vaginal gels. It is advisable to use the rheological optimum to select the type of packaging and method of dosing of vaginal gels according to their rheological characteristics.